The Effect of Nitrous Oxide Anesthesia on Early Postoperative Opioid Consumption and Pain. Issue 1 (1st January 2014) - Duma, Andreas; Helsten, Daniel; Brown, Frank; Bottros, Michael M.; Nagele, Peter
Abstract : Background and Objectives: Many patients experience moderate to severe postoperative pain. Nitrous oxide (N2 O) exerts analgesia by inhibition of N -methyl-D-aspartate receptors. Ketamine, another N -methyl-D-aspartate receptor antagonist, reduces postoperative opioid consumption and pain. A similar effect of N2 O is plausible, yet understudied. The goal of this study was to determine the effects of N2 O anesthesia on early postsurgical opioid consumption and pain. Methods: This was a retrospective, secondary analysis of the Vitamins In Nitrous Oxide trial, where 500 patients undergoing general anesthesia for noncardiac surgery received 60% N2 O and 125 received no N2 O (otherwise, inclusion/exclusion criteria were identical). Exclusion criteria for this study were regional anesthesia, not extubated after surgery, transfer to intensive care unit, no available postanesthesia care unit record, postsurgical sedation, or treated with naloxone. Primary outcomes were cumulative opioid consumption measured in morphine equivalents and pain scores during the immediate recovery phase. Results: Four hundred forty-two patients met inclusion criteria. No difference in intraoperative and postoperative opioid consumption was observed between patients who received N2 O (n = 353) and patients who did not (n = 89). The median [interquartile range] postoperative morphine equivalent dose was 6.7 mg [1.7–14.1 mg] for patients who received N2 O and 6.7 mg [2.1–15.4 mg] for patients who did not ( P = 0.73). The maximum pain score was 6 [4–8] for patients who received N2 O versus 6 [3–8] for patients who received N2 O-free anesthesia ( P = 0.52). The prevalence of moderate to severe pain was 69% for patients who received N2 O and 68% for patients who did not ( P = 0.90). Conclusions: Nitrous oxide anesthesia was not associated with decreased opioid administration, pain, or incidence of moderate to severe pain in the early postoperative phase.